Strengthening teachers’ skills in using an enrichment biology e-module based on flipbook integrated with Qur’anic and Sunnah values - Robiah, Siti; Tambak, Syahraini; Siregar, Juliarni; Hafizah, Jhannah; Swastika, Amelia (Journal of Community Service and Empowerment, 2024)
Biology teachers at MAN 2 Model Pekanbaru still rely on conventional learning resources that do not fully meet the needs of an Islamic-based curriculum. This limitation has an impact on students' ability to internalize Biology concepts within a holistic Islamic framework. Therefore, workshops and interventions are needed through the provision of flipbook-based Biology e-modules integrated with the values ​​of the Qur'an and As-Sunnah to improve the quality of learning and student understanding. This community service aims to improve the capacity of biology teachers' skills at MAN 2 Model Pekanbaru by using flipbook-based biology enrichment e-modules integrated with the values ​​of the Qur'an and As-Sunnah. The partner profile shows that most teachers at MAN 2 Model Pekanbaru have good pedagogical competence, but need to increase their capacity in utilizing digital technology-based learning resources integrated with Islamic values. This condition requires intensive training and mentoring programs for teachers so that they are able to optimize the use of flipbook-based e-modules that are in accordance with the needs of the curriculum and Islamic values. The results of the workshop showed that biology teachers at MAN 2 Model Pekanbaru were in the category of having quite good skills in using e-modules in learning, but they needed to get used to it so that they could become more skilled.